Re-description of larvae of Chostonectes nebulosus (Macleay, 1871) (Coleoptera: Dytiscidae, Hydroporinae, Hydroporini, Sternopriscina) with an identification key to the known larvae of Chostonectes Sharp, 1882 - Tsyrlin, Edward; Carew, Melissa; Alarie, Yves (Zootaxa, 2020)
The second and third larval instars of the Australian endemic dytiscid Chostonectes nebulosus (Macleay, 1871) are described and illustrated for the first time including a detailed chaetotaxic analysis of head capsule and appendages, legs, last abdominal segment and urogomphi. Collected larvae were successfully associated with adults using rearing and a molecular approach. The identification key and COI barcodes for C. nebulosus, C. gigas (Boheman, 1858) and C. johnsonii (Clark, 1862) are provided.